EARLY POSTOPERATIVE MESH-RELATED COMPLICATIONS AFTER PLACING TWO- AND FOUR-SLEEVED SYNTHETIC IMPLANTS IN WOMEN WITH GENITALS PROLAPSE - Эйзенах, Игорь Александрович; Власова, Вероника Валерьевна; Мозес, Вадим Гельевич; Захаров, Игорь Сергеевич (Medicine in Kuzbass, 2017)
Objective – to study the frequency of mesh-related complications when using different forms of synthetic mesh implants and surgical approach in surgery on the pelvic floor in women. Materials and Methods. We studied the frequency of early postoperative mesh-related complications in 233 postmenopausal women with cystocele II-III, to whom synthetic mesh implantswere placed. All patients were divided into three groups: Group A (94 women) included patients with a four-sleevedimplant placed through the longitudinal midline incision on the anterior vaginal wall; Group B (94 women) included patients with a four-sleevedimplant placed through the transverse incision on the cervix 1,5 cm from the cervical canal; Group C (45 women) included patients witha two-sleeved implant placed through the longitudinal midline incision on the anterior wall of the vagina. Conclusions. The use of synthetic mesh implants with two sleeves for the correction of cystocele in women reduces the incidence of postoperative mesh-related complications. In severe prolapse, when the fixation of the implant with two sleeves may not be sufficient the synthetic mesh implants with four sleevesshould be placed through the transverse incision on anterior vaginal wallto reduce the incidence of postoperative mesh-related complications.